Telecommunications and information support in operations - Devetak Saša M.; Karović Samed M. (Војно дело, 2016)
Information is a resource that significantly tailors the preparation, planning and execution of modern military operations. Collection, processing, dissemination and use of information are important contents of successful command and leadership of forces in an operation. Information processed and disseminated in real time increases the speed and effectiveness of command and leadership, reduces the duration of the decision-making cycle, and make it possible to take initiative and supremacy in the operation. The significance of telecommunications and information support proceeds from the information dimension, as an important factor of the operating environment in which the operation is prepared, planned and conducted. It is made possible by telecommunications and information system of the Armed Forces and other holders of telecommunications systems in the area of operation. The paper presents the theoretical bases of determination and content of the telecommunications and information support and highlights its role and importance in the operation. It describes the process of planning, organization and implementation of the telecommunications and information support in the operation.